CUSTOMARY MARRIAGE VS ISLAMIC: LEGAL ANALYSIS AND STATE RECOGNITION IN FUNCTIONAL STRUCTURAL THEORY - Ngazizah, Inna Fauziatal; Dzofir, Mohammad (Universitas 17 Agustus 1945 Semarang, 2025)
This article explores the complex interaction between customary marriage and Islamic marriage within the framework of Indonesian legal pluralism. It seeks to examine the legal validity and state recognition of marriages conducted under customary traditions compared to those performed according to Islamic law. The analysis is grounded in the functional structural theory, which posits that each legal and social institution has a function to maintain societal stability. In Indonesia, where both customary (adat) and Islamic norms operate alongside formal state law, the recognition and regulation of marriage practices become a critical point of inquiry. Through normative-juridical analysis, the study reveals that customary marriages—although socially legitimate within their local communities—often face challenges in obtaining state recognition, particularly in relation to administrative documentation such as marriage certificates and civil rights protections. Meanwhile, Islamic marriages, regulated under the Marriage Law No. 1 of 1974 and administered by the Religious Courts, receive formal recognition when they conform to procedural legal requirements. The article emphasizes the need for the state to harmonize these legal systems to avoid marginalization of indigenous practices while ensuring legal certainty for citizens. Using functional structural theory, the study argues that both customary and Islamic marriage systems serve crucial roles in maintaining social order, identity, and cohesion. Legal pluralism, when managed inclusively, can enhance rather than undermine state authority. Thus, this paper calls for more integrative legal mechanisms that accommodate Indonesia’s socio-cultural diversity without compromising legal clarity or individual rights.